Effects of family functioning, social support and self-efficacy on depressive symptoms - Vyshnavi P. Ramesh; Wu, Shin Ling (Penerbit Universiti Kebangsaan Malaysia, 2022)
Depression is one of the most common mental health issues due to different factors such as family functioning, social support and self-efficacy. There have been opposing views on how these factors affect depressive symptoms. Thus, this study aims to investigate the predicting effects of family functioning, social support and self-efficacy on depressive symptoms among emerging adults in Malaysia. Convenient sampling was used to recruit 214 emerging adults of age 18 to 25 years old. Participants were given a questionnaire which comprised of four scales namely Family Assessment Device (FAD), Multidimensional Scale of Perceived Social Support (MSPSS), General Self-Efficacy Scale (GSE), and Depression Anxiety Stress Scale (DASS). Pearson correlation and multiple regression were used to test the hypotheses. The current study found a weak, significant negative correlation between social support and depressive symptoms as well as a moderate, significant negative correlation between self-efficacy and depressive symptoms. When all 6 dimensions of family functioning (problem solving, communication, roles, affective responsiveness, affective involvement and behavioral control) were tested in the regression model, only roles and problem solving significantly predicted depressive symptoms with roles being the strongest predictor. In another multiple regression analysis, when social support, self-efficacy and all dimensions of family functioning were included simultaneously in the regression model, only roles and social support significantly predicted depressive symptoms with roles being the strongest predictor. Overall, we concluded that among all the factors tested in the current study, roles and social support impacted the most on the development of depressive symptoms.